PENGARUH INOVASI PRODUK DAN PERSEPSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DALAM MENGGUNAKAN KARTU TELKOMSEL - Titi Hasanah (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
Based on surveys conducted on Telkomsel cards used by GraiPari Telkomsel city pagar alam customers, there are still shortcomings, one of which is the Telkomsel card product provides less choice of variants. And perception about Telkomsel card product has its own value for consumers compared to other brands. The majority of consumers provide imperfect judgments, this is likely because consumers have not felt satisfied, comfortable with the product, therefore the author is interested to do peneletian this. Problem formulation in this research is: is there any influence of product innovation to consumer purchasing decision of Telkomsel Card at Graipari Telkomsel city Pagar Alam, is there any consumer perception to consumer purchasing decision of Telkomsel Card at GraiPari Telkomsel city Pagar alam, is there any influence of product innovation and consumer perception to consumer purchasing decision Telkomsel Card at Graipari Telkomsel kota pagar alam. The sample of this research is all consumer of Telkomsel card in Graipari Telkomsel city pagar alam which amounts to 100 people, in period of one month purchase that is in May 2020. Based on the results of data processing using SPSS, the regression equation obtained is :. The value of coefficient of determination (r ^ 2) based on data processing table of SPPS of 0,723. The variables affecting Telkomsel Graipari consumers can be influenced by the variables that exist and the variable with the respondents of 72.3%, while the rest of 27.7% can be taken into account by other variables that are not included in this research model. Variable of product innovation with t count> from t table or 2,725> 2.000, hence Ho is rejected and Hietahui, this indicates that there is significant influence to variables influencing consumer Graipari Telkomsel kota pagar alam. Variable consumer perceptions with t count> of ttable or 2,543> 2,000, then Ho rejected and Hietahui, this indicates that there is significant influence between consumer variable to consumer variable Graipari Telkomsel city pagar alam. Results of data processing with the value of Fcount of 16.729. With the value of F arithmetic> F table. From the hypothesis test results then the decision taken is the same variable and different variables for each consumer who have different variables to consumers Graipari Telkomsel city pagar alam.